Investigation of the hydrodynamic effects of dredging Laguna Lake using numerical modeling - Dita, Andrei Raphael P.
Laguna Lake serves as a floodwater storage reservoir for the entire CALABARZON region and Metro Manila. In times of heavy rainfall occurrences, the lake functions as the main protection system of NCR from flooding. Hydraulic structures such as the Napindan Hydraulic Control Structure and Rosario Weir in the Manggahan Floodway were constructed to regulate flows in and out of the lake. Due to increasing urbanization, sediment transport into the lake has increased over time. This resulted to shoaling and capacity reduction. In order to improve the operational use of Laguna Lake the Arroyo Administration proposed the Laguna Lake Rehabilitation Project. This included dredging 4.6 million ml of silt and waste materials in the West Bay of the lake and Napindan Channel. Hydrodynamic parameters expected to be affected by such innovation include water level elevation, velocity and bed shear stress. Two-dimensional modeling is performed with the aid of Delft3D in order to describe and compare the hydrodynamic condition of the lake for the pre- and post-dredging scenarios. Certain guidelines for the Laguna Lake-Manila Bay system were observed in the modeling process. River discharges into Laguna Lake were incorporated in the model. Tidal forcing from Manila Bay, wind forcing and bottom roughness of the lake were also included in the model. Model calibration period used was 2003 and 2004, with Manning's roughness as the main calibration parameter. Different roughness values were observed for the rivers, lake and residential area. The validated model served as the baseline scenario for the remaining dredge simulations. QUICKIN was used in representing the dredge as a modified bathymetry. Three different dredging scenarios were considered: (1) Deepening of Napindan Channel; (2) Dredging of West Bay shore areas; and (3) Combined dredging of Napindan Channel and West Bay. Time-series plots of water level elevation and depth averaged velocity, and map files of velocity current and bed shear stress showed variation for these different scenarios. Scenarios 1 and 3 displayed attenuation of the water level elevation. During the dry season, the back flow rates through Pasig River were increased which means that salinity intrusion is enhanced, further improving the fishing conditions in the lake. The discharge capacity for both scenanos were higher than the baseline scenario for the wet season. However, Scenario 2 resulted to no observable variation in the water level. The discharge capacity was also found to be lower for this scenario. Bed shear stress at low water levels were higher in all scenarios which may increase sediment transport. It can be concluded that inundation and flood retention duration are effectively reduced by dredging. Dredging the Napindan Channel plays a significant role in enhancing the hydrodynamic conditions of the lake as deeper bathymetries of the channel showed greater water level reduction and cumulative di scharge increase. Scenario 1, among the three scenanos, produced the most improved hydrodynamic conditions of Laguna Lake. This study can be further improved by using the actual dredging plan and more recent and complete data inputs such as bathymetry, discharge, water level, wind effects and evaporation.